Development and characterization of novel alginate-1 based hydrogels as vehicles for bone substitutes - Morais, D. S. (2013)
In this work three different hydrogels were developed to associate, as vehicles, with the synthetic bone substitute GR-HA. One based on an alginate matrix (Alg); a second on a mixture of alginate and chitosan (Alg/Ch); and a third on alginate and hyaluronate (Alg/HA), using Ca2+ ions as cross-linking agents. The hydrogels, as well as the respective injectable bone substitutes (IBSs), were fully characterized from the physical-chemical point of view. Weight change studies proved that all hydrogels were able to swell and degrade within 72 hours at pH 7.4 and 4.0, being Alg/HA the hydrogel with the highest degradation rate (80%). Rheology studies demonstrated that all hydrogels are non-Newtonian viscoelastic fluids, and injectability tests showed that IBSs presented low maximum extrusion forces, as well as quite stable average forces. In conclusion, the studied hydrogels present the necessary features to be successfully used as vehicles of GR-HA, particularly the hydrogel Alg/HA.